Evaluation of Surgical Technique and Clinical Results of a Procedure-Specific Fixation Method for Tibial Tuberosity Transposition in Dogs: 37 Cases - Onis, David; Entoft, Jessica; Wouters, Erik G.H.; Skytte, Ditte; Bruining-Staal, Karin; Vernooij, Johannes C.M.; Meij, Björn Petrus (Veterinary and Comparative Orthopaedics and Traumatology, 2023)
Objective The aim of this study was to describe the use of a procedure-specific fixation method for tibial tuberosity transposition and report clinical outcome.Study Design This is a multi-institutional case series, evaluating 37 cases that were treated surgically for medial patellar luxation (MPL) and in which the tibial tuberosity transposition (TTT) was performed using the Rapid Luxation Plating System (RLPS). Surgical technique, implants, clinical outcome, and complications are reported.Results Surgery was successfully performed in dogs weighing 2.5 to 36.2 kg. Postoperative minor complications occurred in 13 cases (35%) and major complications occurred in 3 cases (8%). No implant-related complications or tibial tuberosity avulsions or fractures were seen. Outcome related to surgery was good or excellent in all cases.Conclusion The RLPS for TTT provides a feasible technique in a large range of patients with MPL and lowers the occurrence of implant-related complications and tibial tuberosity avulsion or fracture.
Keywords: rapid luxation plating system; tibial tuberosity transposition; medial patellar luxation; dog; implant